Catálogo e ferramenta de detecção de Bad smells de desempenho em sistemas React - Barros, Aryclenio Xavier (2023)
The Javascript language is one of the most famous development tools today, gaining visibility in several areas such as web games, three-dimensional renderings, artificial intelligence and, mainly, the development of web applications, with its major role in the construction of interfaces through front end development. In this ecosystem, several libraries and frameworks were built, the most famous being the React library, developed and published by Meta (Facebook). Applications built on React, like any other system, need to remain usable and relevant over time. As empirical evidence shows, the presence of bad smells in the code might compromise the software evolvability. Based on this context, this work presents, based on mapping studies of the academic and gray literature, a proposal of bad smells oriented to the React library, integrating them to a code detection tool called ReactLint, which will flag code flaws and will indicate possible solutions to developers who use it. This work aims to validate the proposed smells, as well as the built tool, in order to identify whether they can affect the performance of a React application in the short and long term.